Analysis of the effect and responsiveness of physiology factors on thermal comfort in an air-conditioned environment - Norfadzilah, Jusoh (2016)
There is no doubt that hot and cold environment can interfere with human activities, affect the task performance and influence productivity of worker in the building. Environmental factors can be utilized to provide the worker comfort while performing their tasks. Previous studies have indicated that the poor environment level decreased workers' performance and increased their health problems. Nowadays, various studies have been conducted to determine the optimal level of environmental factors. But in Malaysia, few studies were conducted involving the Malaysian workers. Furthermore, there are still lacking of studies conducted in finding the relationship between environmental factors and workers in the building, especially in air conditioning ventilation. This study has three objectives; first, to investigate the relationship of thermal comfort and sensation towards human physiology factors (skin temperatures and heart rate) under room temperatures with three task activities. The second objective is to obtain the significance correlation implication of thermal effect to the human physiology factors (skin temperatures and heart rate). And, the final objective is to propose the optimal thermal condition based on human physiological factors (skin temperatures and heart rate). This study was conducted in a closed and controlled environmental chamber. The experiments were carried out with the activities of thinking, sitting while typing and printing at 3.6 m x 2.4 m x 2.4 m of dimension a simulated office in the chamber. This experiment was repeated under the five room temperatures (19 oC, 21 oC, 23 oC, 26 oC and 29 oC) in order to identify the most comfortable temperature for office workers. Fifteen subjects were recruited in this study. The duration of the experiment for each subject is 3 hours 20 minutes. All the studies factors and activities were recorded at an interval of 10 minutes. All the environmental and physiological factors collected data was analyzed using statistical analysis and computer simulation. The study found that the different room temperatures and metabolic rate produced different level of heart rate. It indicates the level of comfort by subjects. Analysis of skin temperature showed that levels of temperatures vary, depending on the body segment considered and the subject. This finding is meaningful in showing the possibility of identifying the most responsive region and using the skin temperature data collected from that point to estimating a subject‟s thermal sensation. Furthermore, this study shows the potential application of this finding for buildings that use mechanical systems (air conditioning ventilation) as an input to generate an optimal set-point temperature so that a subject‟s thermal sensation could be maintained at the neutral level while preventing over cooling or over heating conditions. The optimal thermal condition based on human physiology is 23 oC. At this temperature, the skin temperature and heart rate level shown by each subject are at medium level. So, they are comfortable to do their office tasks and lead to increase in performance. The study contributes towards enhancing understanding of determining effects, modelling and predicting the optimal temperatures for office environments in Malaysia.